Did Structured Credit Fuel the LBO Boom? - SHIVDASANI, ANIL; WANG, YIHUI (Journal of Finance, 2011)
ABSTRACT The leveraged buyout (LBO) boom of 2004 to 2007 was fueled by growth in collateralized debt obligations (CDOs) and other forms of securitization. Banks active in structured credit underwriting lent more for LBOs, indicating that bank lending policies linked LBO and CDO markets. LBO loans originated by large CDO underwriters were associated with lower spreads, weaker covenants, and greater use of bank debt in deal financing. Loans financed through structured credit markets did not lead to worse LBOs, overpayment, or riskier deal structures. Securitization markets altered banks' access to capital, affected their lending policies, and fueled the recent LBO boom.